Effect of Triple Antibiotic Paste, Double Antibiotic Paste, and Calcium Hydroxide on Antibiotic Resistance of Tet Repressor Proteins, Tetracycline Resistance Gene W, and Tetracycline Resistance Gene Q: A Randomized Controlled Clinical Trial - Karataş, Ertuğrul; Kırmızıbekmez, Özgen; Baltacı, Mustafa Özkan; Adıgüzel, Ahmet (Journal of Dentistry Indonesia, 2023)
Objective: To investigate the effect of the use of Calcium Hydroxide (Ca(OH)2), Triple Antibiotic Paste (TAP), and Double Antibiotic Paste (DAP) as intra-canal medicaments on the development of antibiotic resistance by evaluating tetracycline genes. Methods: Forty five patients were randomly assigned into 3 groups according to the intracanal medication using a web program (www.randomizer.org), (Ca(OH)2, TAP and DAP). Root canal bacteriological samples were collected before root canal treatment (S1) and after chemo-mechanical procedures (S2). Following root canal shaping procedures, intra-canal medication of the root canals was performed with selected intra-canal medicament. A second appointment was planned for the patients 15 days later. At the second appointment, the medication was removed mechanically and after irrigation of the root canals, the post medication samples (S3) were collected. Bacteriological samples were then investigated for bacterial counts and antibioticresistant genes [Tet Repressor proteins (TetR), Tetracycline resistance gene W (TetW) and Tetracycline resistance gene Q (TetQ)] using polymerase chain reaction (PCR), and the data were statistically analyzed. The Friedman, Kruskall-Wallis and chi-square tests were used. These genes were selected as the difference between TAP and DAP is that TAP contains tetracycline and tetracycline resistance is governed by tet genes. Results: There was no statistically significant difference among the samples (S1, S2, and S3) in terms of the number of root canals positive for antibiotic resistance genes in both the Ca(OH)2 and DAP groups. However, the number of root canals positive for TetR gene increased significantly (6 [40%] to 12 [86%]) following intra-canal medication with TAP. Conclusion: It can be concluded that 15 of days intra-canal medication with TAP causes tetracycline resistance. In contrast, DAP does not cause tetracycline resistance and it has similar antibacterial effectiveness to TAP. The DAP would be the choice of medicament rather than TAP in clinical practice.